HTML5 PDF FLIP ELECTRONIC MODULE ON VIRUS CONCEPT FOR HIGH SCHOOL STUDENTS - Melati Mawar; Kaspul Kaspul; Bunda Halang (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Electronic module based on PDF FLIP HTML5 is a form of presenting independent teaching materials that are systematically arranged into electronic format and make all the contents interactive. The purpose of this study is to describe an electronic module of teaching materials that can be developed about the concept of a virus in high school. This study uses the Research and Development method with a 4D model, that is limited to develop phase. The results of the validation of the developed electronic module are declared valid from an average validity of 83.87%. The results of the practicality of the response of 9 students obtained results of 82.02% and were categorized as very practical.